PERAN AKTIF WANITA DALAM PENINGKATAN PENDAPATAN RUMAH TANGGA MISKIN: STUDI KASUS PADA WANITA PEMECAH BATU DI PUCANGANAK KECAMATAN TUGU TRENGGALEK * - Haryanto, Sugeng (Universitas Muhammdaiyah Surakarta, 2008)
This research explain how women share actively in the effort increasing earnings of the household. This research done with taking sample at the stone crusher women in Kecamatan Tugu Kabupaten Trenggalek. Women have potency in giving contri-bution of earnings of household, especially impecunious household. In impecunious household, women household member plunge to job market for adding earnings household felt insufficient. Women contribution can be told as safety valve or sup-porter for impecunious household to fulfill everyday basic need. This research aim 1) for analyzing contribution of earnings of stone crusher worker women to earn-ings of family, 2) to know usage of earnings of stone crusher worker women, 3) to know in working which poured by stone crusher worker women. Research finding indicate that women who work as stone crusher have enough significant earnings contribution to earnings of family.